The Influence Of Local Own-Source Revenue, Revenue Sharing Funds And Special Allocation Funds On GDRP In Pesisir Barat Districts Of Lampung Province - Hardiansyah Batubara, Masma Noor; Marselina; Toto Gunarto (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Decentralization of policies provides great opportunities for regions to improve financial conditions. Efforts to increase regional revenues by paying attention to regional economic development, one of which is Regional Original Income (PAD), Profit Sharing Funds (DBH), Special Allocation Funds (DAK), and other legitimate income are other sources of income which are believed to encourage government to increase economic growth and community needs, especially the West Coast district. This research is quantitative descriptive in nature, with secondary data, Pesisir Barat Regency as the research observation area. The research was carried out with data from quarters 1 to 4 for 9 years time series from the period 2014: Quarter 1 - 2023: Quarter 4. The data is in the form of a timeseries so the methodology used is Ordinary Least Square (OLS) and Error Correction Model (ECM) . The research results show that regional original income (PAD) has a positive and significant influence on the long-term relationship with gross regional domestic product (GRDP), and does not have a positive and significant influence on the short-term relationship. Profit Sharing Funds (DBH) have a positive and significant influence on the long-term relationship with gross regional domestic product (GRDP), and have a positive and significant influence on the short-term relationship. Special Allocation Funds (DAK) have a positive and significant influence on the long-term relationship with gross regional domestic product (GRDP), and have a positive and significant influence on the short-term relationship.